Valproic Acid Enhances Reprogramming Efficiency and Neuronal Differentiation on Small Molecules Staged-Induction Neural Stem Cells: Suggested Role of mTOR Signaling - Qingrui Duan; Siyi Li; Xinrui Wen; Gavin Sunnassee; Jian Chen; Sheng Tan; Yang Guo (Frontiers in Neuroscience, 2019)
Inducing somatic cells into neural stem cells (iNSCs) in specific ways provides a new cell therapy in a variety of neurological diseases. In the past, iNSCs were generated by transcription factors which increased the risk of mutagenesis, tumor formations, and immune reactions by viral transduction vectors. Therefore, in this study, different small molecules were used to induce mouse embryonic fibroblasts (MEFs) into iNSCs in different reprogramming stages, which showed high reprogramming efficiency without altering the genome. We demonstrated that the small molecules staged-induction neural stem cells (SMSINS) have the characteristics of neural stem cells (NSCs) in morphology, gene expression, self-renewal and differentiation potential. Furthermore, valproic acid (VPA), one of small molecules, was showed to enhance neural induction with highest efficiency compared with six other small molecules, which were also investigated in the present study. Moreover, our results suggested that activating the mammalian target of rapamycin (mTOR) signaling enhanced the induction efficiency and neuronal differentiation. Collectively, our findings indicated that using this induction program allowed us to obtain safe and efficient iNSCs which were free of genetic manipulation. The VPA-mediated mTOR signaling pathway may enhance reprogramming efficiency and neuronal differentiation. So we suggested that this program could be a new method of obtaining iNSCs for the treatment of neurological diseases by cell replacement therapy in the future.